2011
DOI: 10.1016/j.juro.2011.04.079
|View full text |Cite
|
Sign up to set email alerts
|

SEER Coding Standards Result in Underestimation of Positive Surgical Margin Incidence at Radical Prostatectomy: Results of a Systematic Audit

Abstract: In this SEER registry 30% of radical prostatectomy cases in 2007 were coded inaccurately. SEER coding guidelines result in underestimating the positive surgical margin incidence. Clinicians and investigators should recognize the limitations of tumor registry data on positive surgical margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…However, others have found that coding errors in the SEER database do not significantly change the composition of patients with pT2 vs. pT3 disease [37]. It is also possible that there are inaccuracies in the clinical staging of patients, such as the determination by clinical examination of ECE.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have found that coding errors in the SEER database do not significantly change the composition of patients with pT2 vs. pT3 disease [37]. It is also possible that there are inaccuracies in the clinical staging of patients, such as the determination by clinical examination of ECE.…”
Section: Discussionmentioning
confidence: 99%
“…First, recent work from one of the SEER sites has suggested that the SEER data may underreport PSM. 26 Information regarding comorbidities was not available and several groups have reported that increased body mass index is associated with an increased risk of PSM. 21,27,28 The location and number of positive cores from transrectal ultrasound (TRUS) guided biopsies of the prostate guide surgeons with surgical planning.…”
mentioning
confidence: 99%
“…The introduction of these codes, as well as the corresponding coding guidelines, should resolve the previously observed underestimation of the incidence of positive surgical margins at radical prostatectomy. 23 Given that preoperative PSA has been incorporated into AJCC 7th edition staging, it may seem somewhat surprising that 1.3% of prostate cancer patients diagnosed in 2010 did not receive a PSA test and that an additional 15.2% have unknown values (Table 1). This finding indicates that central cancer registries are not completely capturing information from physician urology practices.…”
Section: Discussionmentioning
confidence: 99%